EFFICACY OF INTRALESIONAL ACYCLOVIR VERSUS CRYOTHERAPY FOR TREATMENT OF PLANTAR WARTS - Ahmad, Faisal; Janjua, Natasha Shahid; Rizwan, Muneeza (Journal of Ayub Medical College Abbottabad, 2026)
Background: Warts, benign proliferation of skin and mucosa caused by human papilloma virus (HPV), are treated by different modalities among which cryotherapy remains the most common. The objective of this study was to assess comparative efficacy of Intralesional acyclovir versus cryotherapy for plantar warts. Methods: This quasi-experimental study was conducted on eighty-four patients of plantar warts (1–10 in number) enrolled after obtaining ethical approval and written informed consent. Patients were divided into group A and B. Group A patients received intralesional Acyclovir in a dose of 0.1ml (70 mg/ml) at the base of each wart while Group B patients had cryotherapy for two freeze and thaw cycles with each cycle of 10 seconds duration. Lesion size and clinical photographs were recorded at baseline and at follow-up visits scheduled every 2 weeks (maximum 5 sessions) and followed for further 4 months. Response was considered as complete (100% resolution), partial (resolution 50-99%) or no response (resolution <50%). Results: A total of 84 patients with 42 (79% Males and 21% females) in group A and 42 (55% males and 45% females) in group B, having mean age 27.79±4.36 and 26.74±6.03 years, mean wart size 0.43±0.09 and 0.49±0.09 cm and mean number of warts 1.61±1.06 and 1.67±1.12 in each group respectively. 83% achieved complete response, 10% lost to follow-up and 7% refused treatment in Group A whereas 48% achieved complete and partial responses respectively and 4% had no response in Group B (p<0.001). Conclusion: Acyclovir is an effective treatment modality of cutaneous warts with better results in males presenting with single plantar wart.